Harmonising Food Frequency Questionnaire (FFQ) for South East Asia for Accurate Dietary Data Interpretation - Hamid Jan Jan Mohamed (Indonesian Nutrition Association, 2020)
South East Asia (SEA) is an ethnically diverse region but still share some similarities with regards to food intake1. Each country within SEA can be considered as food heaven with its diversity of dietary choices and creativity in food preparations. Within SEA, each individual country is also unique due to its culture, tradition and food choice. Additionally, cross country immigration for economic purpose also demand healthcare providers of host country some additional tasks for evidence-based dietary advice as their training were mostly focused at local foods. For researchers on regional dietary intake huge challenge appears when comparison between countries are made with regards to dietary intake. It raises two pertinent questions. Is it correct to compare food date collected using unstandardized dietary intake tool? Is it possible to harmonise the dietary data and produce a FFQ as a standard tool?